FAK inhibition protects condylar cartilage under excessive mechanical stress. (4th August 2020) - Yanoshita, Makoto; Hirose, Naoto; Sumi, Chikako; Takano, Mami; Nishiyama, Sayuri; Tsuboi, Eri; Onishi, Azusa; Yamauchi, Yuka; Asakawa, Yuki; Ryo, Kunimatsu; Tanimoto, Kotaro
Abstract: Objectives: Excessive mechanical stress is assumed to be a major cause of temporomandibular joint (TMJ) osteoarthritis (OA). +Focal adhesion kinase (FAK) is a cytoplasmic non‐receptor tyrosine kinase involved in a variety of signaling pathways. Little has been reported on the function of FAK in TMJ‐OA. In the present study, we investigated the effect of FAK inhibition on TMJ cartilage under excessive mechanical loading stress. Materials and Methods: Articular cartilage explants were harvested from the TMJ of rats and subjected to mechanical loading in the presence of an FAK inhibitor in organ culture. The gene expression of inflammatory cytokines was examined after the application of mechanical loading with or without FAK inhibitor. Paraffin‐embedded sections of articular cartilage were stained with hematoxylin and eosin, safranin O and fast Green, toluidine blue, TUNEL staining, and immunohistochemical staining and was performed to investigate the protein expression of IL‐1β and MMP‐13. Results: Treatment with FAK inhibitor reduced the gene expression of inflammatory cytokines and inhibited the degradation of articular cartilage, as determined histologically. FAK inhibitor treatment also suppressed the protein expression of IL‐1β and MMP‐13 in the hypertrophic zone, as determined immunohistologically. Conclusion: Treatment with FAK inhibitor suppresses inflammation and protects condylar cartilage under excessive mechanical loading.